A New Antifungal-Loaded Sol-Gel Can Prevent Candida albicans Prosthetic Joint Infection - Hugo Garlito-Díaz; Jaime Esteban; Aranzazu Mediero; Rafael Alfredo Carias-Cálix; Beatriz Toirac; Francisca Mulero; Víctor Faus-Rodrigo; Antonia Jiménez-Morales; Emilio Calvo; John Jairo Aguilera-Correa (MDPI AG, 2021)
Fungal PJI is one of the most feared complications after arthroplasty. Although a rare finding, its high associated morbidity and mortality makes it an important object of study. The most frequent species causing fungal PJI is C. albicans. New technology to treat this type of PJI involves organic-inorganic sol-gels loaded with antifungals, as proposed in this study, in which anidulafungin is associated with organophosphates. This study aimed to evaluate the efficacy of an anidulafungin-loaded organic-inorganic sol-gel in preventing prosthetic joint infection (PJI), caused by Candida albicans using an in vivo murine model that evaluates many different variables. Fifty percent (3/6) of mice in the C. albicans-infected, non-coated, chemical-polished (CP)-implant group had positive culture and 100% of the animals in the C. albicans-infected, anidulafungin-loaded, sol-gel coated (CP + A)-implant group had a negative culture (0/6) (p = 0.023). Taking the microbiology and pathology results into account, 54.5% (6/11) of C. albicans-infected CP-implant mice were diagnosed with a PJI, whilst only 9.1% (1/11) of C. albicans-infected CP + A-implant mice were PJI-positive (p = 0.011). No differences were observed between the bone mineral content and bone mineral density of noninfected CP and noninfected CP + A (p = 0.835, and p = 0.181, respectively). No histological or histochemical differences were found in the tissue area occupied by the implant among CP and CP + A. Only 2 of the 6 behavioural variables evaluated exhibited changes during the study: limping and piloerection. In conclusion, the anidulafungin-loaded sol-gel coating showed an excellent antifungal response in vivo and can prevent PJI due to C. albicans in this experimental model.